Efektifitas Layanan Konseling Kelompok dengan Teknik Self Instruction untuk Mengurangi Prasangka Sosial Peserta Didik di SMA Negri 2 Palangka Raya: The Effectiveness Of Groups Conselvation Services Using Self Instruction Techniques To Reduce Students 'Social Preliminary In SMA 2 Palangka Raya - Puspita Ayu Prida; Dina Fariza Tryani Syarif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to: (1) Know the level of social prejudice that occurs between students before and after being given service, (2) Knowing group counselling services with Self instruction techniques can reduce students' social prejudice. The type of research used was Experimental Research. The subjects in this study were class X students of SMA N 2 Palangka Raya in the 2016/2017 academic year, which amounted to 8 students. Data collection techniques used are scale and observation. Data analysis using hypothesis testing paired sample t-test. The pretest results showed that students' social prejudice scale scoring was 77.50, which was included in the category of social prejudice which was quite high while the suspension of posttest scores of students was 66.75 included in the medium category. From these data shows that there is a decrease in the level of social prejudice of students after the group counselling service intervention is carried out with self-instruction techniques.